Development and implementation of a Python functions for automated chemical reaction balancing - Pankaj Dumka; Rishika Chauhan; Dhananjay R. Mishra; Feroz Shaik; Pavithra Govindaraj; Abhinav Kumar; Chandrakant Sonawane; Vladimir Ivanovich Velkin (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Chemical reaction balancing is a fundamental aspect of chemistry, ensuring the conservation of mass and atoms in reactions. This article introduces a specialized Python functions designed for automating the balancing of chemical reactions. Leveraging the versatility and simplicity of Python, the module employs advanced algorithms to provide an efficient and user-friendly solution for scientists, educators, and industry professionals. This article delves into the design, implementation, features, applications, and future developments of the Python functions for automated chemical reaction balancing. The functions thus developed were tested on some typical chemical reactions and the results are the same as that in the literature.